2019
DOI: 10.1103/physrevmaterials.3.054804
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in Li-intercalated 1TSnSe2 driven by electric field gating

Abstract: Creating carrier reservoirs in layered compounds can effectively tune the carrier density, which often induces a variety of emergent properties. Based on solid-ion-conductor gating technique, we successfully induce superconductivity of 4.8 K in ultrathin Li-intercalated SnSe2 samples. The Li + ions are driven in between interspacing of SnSe2 layers and form a single reservoir layer to provide electrons. In addition, a dome-like T c is found through substituting of S for Se, where the optimal T c is 6.2 K for S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 49 publications
(51 reference statements)
2
22
0
Order By: Relevance
“…The superconducting state is observed to emerge at 18.6 GPa and to reach a maximum T c of about 6.1 K, which remains nearly constant in a large pressure range between 30.1 and 50.3 GPa. Earlier studies have demonstrated superconductivity in bulk and thin films SnSe 2 through intercalation and gating 13,[90][91][92] as well as interface superconductivity in SnSe 2 /ion-liquid and SnSe 2 /graphene 93,94 .…”
Section: Superconducting Propertiesmentioning
confidence: 99%
“…The superconducting state is observed to emerge at 18.6 GPa and to reach a maximum T c of about 6.1 K, which remains nearly constant in a large pressure range between 30.1 and 50.3 GPa. Earlier studies have demonstrated superconductivity in bulk and thin films SnSe 2 through intercalation and gating 13,[90][91][92] as well as interface superconductivity in SnSe 2 /ion-liquid and SnSe 2 /graphene 93,94 .…”
Section: Superconducting Propertiesmentioning
confidence: 99%
“…[ 93 ] However, the large radius of F ion impedes its intercalation into 2D materials, given that the intercalation reported may be from the defects in the Basal plane of 2D materials. Subsequently, solid ion conductors containing Li or Na ions are introduced to SIC‐FETs, [ 45–47 ] in which the carrier densities and phase transitions of 2D layered materials can be tuned by driving Li/Na ions in and out of the thin flakes via electrochemical gating. For example, by controlling the Li ion intercalation, a semiconductor–superconductor transition in Li‐intercalated SnSe 2 and a superconducting phase diagram of FeSe have been reported.…”
Section: Approaches For Electrochemical Intercalation Of Foreign Speciesmentioning
confidence: 99%
“…For example, by controlling the Li ion intercalation, a semiconductor–superconductor transition in Li‐intercalated SnSe 2 and a superconducting phase diagram of FeSe have been reported. [ 45–47 ] More importantly, compared with the former approaches, the electrochemical intercalation process is more reversible due to the stability of solid ion conductor and interface between the channels and SIC, rendering it more appropriate for room‐ and low‐temperature transport measurements. It deserves to be noted that besides the transport measurements, in our opinion, the SIC based intercalation approach will take effect in the characterization of intercalation kinetics and stages by in situ tip‐based techniques, such as atomic force microscopy (AFM), scanning tunneling microscopy (STM), scanning electrochemical microscopy (SECM), and other near field optics, in order to better reveal the structural evolution during the de/intercalation.…”
Section: Approaches For Electrochemical Intercalation Of Foreign Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the transition of TMD and main-group metal dichalcogenide flakes from the normal (resistive) to superconductive phase have been studied in experiments [7][8][9][10][11][12][13][14][15] . However, in the range of temperature close to the phase transition, T T c , the behaviour of TMD flakes in the electromagnetic (EM) field has not been completely studied experimentally, as well as theoretically.…”
Section: Introductionmentioning
confidence: 99%